전자빔 표면 조사에 따른 SnO₂/Ag/SnO₂ 박막의 특성 연구 - 장진규(Jin-Kyu Jang); 김현진(Hyun-Jin Kim); 최재욱(Jae-Wook Choi); 이연학(Yeon-Hak Lee); 공영민(Young-Min Kong); 허성보(Sung-Bo Heo); 김유성(Yu-Sung Kim); 김대일(Daeil Kim) (Biuletyn Uniejowski, 2021)
SnO2 30/Ag 15/SnO2 30 nm(SAS) tri-layer films were deposited on the glass substrates with RF and DC magnetron sputtering and then electron beam is irradiated on the surface to investigate the effect of electron bombardment on the opto-electrical performance of the films. electron beam irradiated tri-layer films at 1000 eV show a higher figure of merit of 2.72×10-3 Ω-1 than the as deposited films due to a high visible light transmittance of 72.1% and a low sheet resistance of 14.0 Ω/□, respectively. KCI Citation Count: 4